Pathophysiology - Copstead, Lee Ellen (Elsevier, 2013)
Explores the etiology, pathogenesis, clinical manifestations, and treatment of disorders. This title provides units that are organized by body system, and each begins with an illustrated review of anatomy and normal physiology. It follows on disease processes and abnormalities that may occur, with a focus on the pathophysiologic concepts involved.